Four-Year Longitudinal Study of Motor and Non-motor Symptoms in LRRK2-Related Parkinson's Disease - Deng, Xiao; Xiao, Bin; Li, Hui-Hua; Ng, Ebonne; Lo, Yew-Long; Tan, Eng-King; Prakash, Kumar M. (Frontiers in Neurology, 2020)
Objectives: In a prospective 4 year study, we evaluated the progression of motor and non-motor symptoms in Parkinson’s disease (PD) patients with Asian-specific LRRK2 risk variants and in non-carriers. Methods: A total of 202 patients with PD, including 133 risk variant carriers and 69 non-carriers, were followed up and evaluated using Modified Hoehn and Yahr (H&Y) staging scale, Unified Parkinson’s Disease Rating Scale (UPDRS) part III, Non-Motor Symptom Scale (NMSS), Parkinson’s disease Questionnaire-39 item version (PDQ-39). Means of generalized estimating equation (GEE) model was performed to compare the differences from baseline between LRRK2 risk variant carriers and non-carriers. Results: Our longitudinal analysis revealed risk variant carriers exhibited greater progression than non-carriers after 3 years based on the modified H&Y staging scale(risk variants carriers: 0.65, non-carriers: 0.06, P=0.041). Meanwhile, UPDRS gait and posture score in risk variant carriers also showed greater increase than in non-carriers, though the difference was not statistically significant. Non-carriers experienced a transient improvement in non-motor symptoms at the early stage of PD, as scores at visit 2 significantly reduced compared to baseline in NMSS domain 3 (mood/apathy), PDQ-39 domain 3 (emotional well-being) and frequency of NMS in non-carriers but not in risk variants carriers. Conclusions: PD gene risk variant carriers were more likely to progress faster in their motor severity than non-carriers. There were transient differences in certain non-motor symptoms and quality of life in carriers. However, more studies are warranted to assess the association of PD risk variants and progression of non-motor symptoms.